Evaluasi Kepuasan Pelanggan dengan Integrasi Metode Quality Function Deployment (QFD) dan Failure Mode And Effect Analysis (FMEA) (Studi Kasus: Kopiria Ahmad Yani Samarinda) - Putra, Luis Fernando; Widada, Dharma; Utomo, Dutho Suh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Kopiria is a coffee shop made from the processed milk coffee segment or what is now usually called contemporary coffee. Good service can influence customer satisfaction, so it is important for shops to pay attention to customer satisfaction, in order to satisfy their customers and be able to compete with competing coffee shops. This makes it necessary to carry out an improvement analysis using the QFD method to determine customer satisfaction problems with improvements that must be made as well as the FMEA method to identify potential failures in the service process in order to maintain and increase the number of customers interested in visiting this coffee shop. The results of processing the attributes of the interests of consumers' desires which were integrated using the FMEA method obtained 5 suggestions for improving customer satisfaction in service, namely monitoring the implementation of Production SOPs, routine employee training, installing generator sets, installing automatic door closers, and increasing parking security.